Digital Narratives During the Pandemic: TV Series, Social Media, and Conversations on the Internet - Martínez-Borda, Rut; de-la-Fuente, Julián; Lacasa, Pilar (Frontiers in Psychology, 2021)
The situation of lockdown experienced during the months from March to June 2020 changed the daily lives of people in Spain and their leisure circumstances. This study analyses the narrative representations that people construct when they watched streaming TV series, during the covid-19 pandemic. To access these representations, the Spanish texts that appear on the Internet are analysed, including social networks and other social media. The paper adopts quantitative approaches that use big data analysis complemented with other qualitative approaches and inspired by content and discourse analysis. Findings show that these narrative representations constructed through conversations are on three levels in which context is revealed: first, institutional and community; second, online or offline interpersonal relationships which mention people as facts or as aspirations of their daily lives; and third, personal lives in the reconstruction of the series, projected on the plot reconstruction and the identity of the actors.